2023
DOI: 10.1182/blood.2022019254
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent pembrolizumab with AVD for untreated classical Hodgkin lymphoma

Abstract: Concurrent administration pembrolizumab with chemotherapy in untreated classical Hodgkin lymphoma (CHL) has not previously been studied. To investigate this combination, we conducted a single arm study of concurrent pembrolizumab with AVD (APVD) for untreated CHL. We enrolled 30 patients (6 early favorable, 6 early unfavorable, and 18 advanced stage, median age 33 years (range 18-69 years)) and met the primary safety endpoint with no observed significant treatment delays in the first two cycles. Twelve patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 41 publications
2
31
2
Order By: Relevance
“…Guidelines are often institution specific and vary across inhibitor may also reduce the number of patients who will require this therapy. 19,20 The use of these frontline agents also impacts the salvage chemotherapy options used to induce remission ahead of ASCT.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines are often institution specific and vary across inhibitor may also reduce the number of patients who will require this therapy. 19,20 The use of these frontline agents also impacts the salvage chemotherapy options used to induce remission ahead of ASCT.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…no active cardiopulmonary symptoms or marked organ dysfunction identified on non‐invasive cardiopulmonary testing), and social health/support (no active substance abuse disorder, presence of a caregiver able to support for at least first 2 weeks following hospital discharge from transplant). Recently, improvements in survival and relapse in the front‐line setting with the incorporation of brentuximab to standard chemotherapy (doxorubicin, vinblastine, dacarbazine [AVD]) and with nivolumab‐AVD, a programmed‐death 1 inhibitor may also reduce the number of patients who will require this therapy 19,20 …”
Section: Autologous Stem Cell Transplantationmentioning
confidence: 99%
“…However, the paradigm of response-adapted therapy, which relies on positron emission tomography (PET) scans for response assessment after cycle 2 (PET2), presents challenges in the context of ICIs. Multiple trials combining ICIs with chemotherapy have indicated that PET2 does not predict treatment response as well as cytotoxic chemotherapy & targeted therapy alone ( 11 ). This discrepancy has been attributed to the higher PET2 positive rate observed in the presence of ICIs, which has not been associated with lower progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy has been attributed to the higher PET2 positive rate observed in the presence of ICIs, which has not been associated with lower progression-free survival (PFS). As an alternative, circulating tumor DNA (ctDNA) analysis has emerged as a more reliable predictor of response, suggesting the potential for integrating ctDNA into risk stratification models ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 In ECHELON-1, patients treated with A + AVD compared with ABVD had a 41% reduction in the risk of death (HR: 0.59; 95% CI: 0.40-0.88; p = 0.009). As of late 2023, studies are evaluating other front-line treatments in patients with advanced-stage cHL [10][11][12][13][14] ; however, results from these studies are immature and available only as conference proceedings.…”
mentioning
confidence: 99%